Molecular and cellular factors control signal transduction via switchable allosteric modulator proteins (SAMPs) - Babel, Heiko; Bischofs-Pfeifer, Ilka (BMC systems biology, 2016)
Rap proteins from Bacilli directly target response regulators of bacterial two-component systems and modulate their activity. Their effects are controlled by binding of signaling peptides to an allosteric site. Hence Raps exemplify a class of monomeric signaling receptors, which we call switchable allosteric modulator proteins (SAMPs). These proteins have potential applications in diverse biomedical and biotechnical settings, but a quantitative understanding of the impact of molecular and cellular factors on signal transduction is lacking. Here we introduce mathematical models that elucidate how signals are propagated though the network upon receptor stimulation and control the level of active response regulator.
Gesehen am 19.08.2020